Q: What is 0 x 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x^2 - 4x -12 = 0 (x + 2) (x - 6) = 0 x + 2 = 0 or x - 6 = 0 x + 2 - 2 = 0 -2 or x - 6 + 6 = 0 + 6 x = -2 or x = 6

x^2 + 12x + 36 = 0(x + 6)(x + 6) = 0(x + 6)^2 = 0√(x + 6)^2 = ± √0x + 6 = 0x + 6 - 6 = 0 - 6x = 6

6 x 0 x 5 = 0 (6 x 0) = 0 (0 x 5) = 0 So your answer is zero.

9x-53=6/x 9x2-53x=6 9x2-53x-6=0 9x2+x-54x-6=0 x(9x+1)-6(9x+1)=0 (9x+1)x(x-6)=0 9x+1=0 or x-6=0 9x=-1 or x=6 x=-1/9 or x=6

6 x 0 x 5 = 0 Because any number multiplied by 0 is equal to zero, 6 x 0 = 0 and then 0 x 5 = 0.

Related questions

x^2 - 4x -12 = 0 (x + 2) (x - 6) = 0 x + 2 = 0 or x - 6 = 0 x + 2 - 2 = 0 -2 or x - 6 + 6 = 0 + 6 x = -2 or x = 6

x^2 - 4x -12 = 0 (x + 2) (x - 6) = 0 x + 2 = 0 or x - 6 = 0 x + 2 - 2 = 0 -2 or x - 6 + 6 = 0 + 6 x = -2 or x = 6

it is 0 because 6 x 0 =0 then 0 x 5 =0

the answer is : 06 x 6 + 6 x 0, if you follow the order of operations, is (6 x 6) + (6 x 0), which is 36+0, which is 36

x=-6+6=0 then x=-2+2=0 and 0+0=0

x^2 + 12x + 36 = 0(x + 6)(x + 6) = 0(x + 6)^2 = 0√(x + 6)^2 = ± √0x + 6 = 0x + 6 - 6 = 0 - 6x = 6

6 x 0 x 5 = 0 (6 x 0) = 0 (0 x 5) = 0 So your answer is zero.

x2 + 5x =6 x2+5x -6 = 0 (x+6)(x-1) = 0 x+ 6 = 0 x = -6 x-1 = 0 x = 1

9x-53=6/x 9x2-53x=6 9x2-53x-6=0 9x2+x-54x-6=0 x(9x+1)-6(9x+1)=0 (9x+1)x(x-6)=0 9x+1=0 or x-6=0 9x=-1 or x=6 x=-1/9 or x=6

In either of these two ways:(3 x 109) + (0 x 108) + (6 x 107) + (0 x 106) + (0 x 105) + (6 x 104) + (6 x 103) + (9 x 102) + (0 x 101) + (0 x 100).(3 x 1000000000) + (0 x 100000000) + (6 x 10000000) + (0 x 1000000) + (0 x 100000) + (6 x 10000) + (6 x 1000) + (9 x 100) + (0 x 10) + (0 x 1).

Equate it to zero (0) , and you have a quadratic equation that can be factotred. Hence x^2 + 12x + 36 = 0 (x + 6)(x + 6) = 0 Hence x = -6

If a polynomial has factors x-6 and x-3 it will equal 0 if either factor equals 0 since the other factor then would be multiplied by 0. ie. 0 * (x-6)=0 and 0 * (x-3)=0. so x=3 or 6